Diversity in diploid, tetraploid and mixed diploid-tetraploid populations of paspalum simplex - Brugnoli, Elsa Andrea (2013)
Fil: Brugnoli, Elsa Andrea. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.